UNCLEAR ADVANTAGES IN THE TASKS OF ACCEPTANCE OF DECISIONS IN THE CONDITIONS OF VAGUENESS - Никифорчин, Ірина Володимирівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
A formal model of decision making support under uncertainty based on fuzzy preferences is presented. Relations with idempotent generalizations of convexity are established.